Вплив тиску на міграцію кисню поблизу кремнієвої поверхні (100) SiC - Токій, В.В.; Савіна, Д.Л.; Токій, Н.В. (Физика и техника высоких давлений, 2013)
Побудовано атомну модель осередку поверхні карбіду кремнію з дефектами. Застосовано пакет програм ABINIT-інструменту nanoHUB з використанням теорії функціонала густини. Встановлено: зі зростанням всебічного тиску найбільшою мірою змінюється внесок локальної електрон-іонної взаємодії у повну енергію осередку; контролюючим механізмом впливу всебічного тиску на міграцію кисню є нелокальна псевдопотенціальна взаємодія валентних електронів з іонним остовом усіх атомів осередку. Передбачено, що збільшення всебічного стиснення призводить: до зміни напрямку процесу оксидизації приповерхневого С-прошарку кремнієвої поверхні карбіду на протилежний – його деоксидизацію; до уповільнення міграції кисню як при оксидизації, так і при деоксидизації приповерхневого С-прошарку кремнієвої поверхні карбіду. Построена атомная модель ячейки поверхности карбида кремния с дефектами. Применен пакет программ ABINIT-инструмента nanoHUB с использованием теории функционала плотности. Установлено: наиболее изменяется вклад локального электрон-ионного взаимодействия в полную энергию ячейки с ростом всестороннего давления; контролирующим механизмом влияния всестороннего давления на миграцию кислорода является нелокальное псевдопотенциальное взаимодействие валентных электронов с ионным остовом всех атомов ячейки. Предсказано, что увеличение всестороннего сжатия приводит: к изменению направления процесса оксидизации приповерхностного С-слоя кремниевой поверхности карбида на противоположный − его деоксидизацию; к замедлению миграции кислорода как при оксидизации, так и при деоксидизации приповерхностного С-слоя кремниевой поверхности карбида. The study was aimed at ascertainment of physical causes that control defect structure formation and properties of nanocrystalline silicon carbide powders. An atomic model of a cell of silicon carbide surface with defects was built. Software package ABINIT−nanoHUB tool was applied with using density functional theory. The changes in total energy at motion of the oxygen atoms in the surface layers of silicon covering of carbide by the vacancy mechanism with increasing hydrostatic pressure were evaluated. It was established that: 1. The contribution of the local electron-ion interaction to the total energy of the cell was changed most of all with increasing hydrostatic pressure. 2. The contributions of the local electron-ion interaction and the exchange-correlation energy of the valence electrons reduced the total energy of the cell with increasing hydrostatic pressure. The contributions of the electron-electron Coulomb Hartree energy, the kinetic energy of the valence electrons, Ewald energy and the energy correction of the ion core of all atoms increased it. 3. The controlling mechanism of the influence of hydrostatic pressure on the migration of oxygen was a non-local pseudopotential interaction of valence electrons with the ionic core of all the atoms in a cell.